Metamitron and shade effects on leaf physiology and thinning efficacy of Malus X domestica Borkh - Rosa, Nídia (2021)
Thinning strategies, namely shade or photosynthetic inhibitors, rely on the reduction of carbon supply to the fruit below the demand, causing fruit abscission. In order to clarify the subject, seven field trials were carried out in Lleida, Girona, and Sint-Truiden (2017 + 2018), using orchards of ‘Golden’ and ‘Gala’ apple trees. At the stage of 9–14-mm fruit diameter, four treatments were implemented: (A) CTR-control, trees under natural environmental conditions; (B) SN-shaded trees, trees above which shading nets reducing 50% of irradiance were installed 24 h after metamitron application date—without application of metamitron—and removed after five days; (C) MET-trees sprayed with 247.5 ppm of metamitron; (D) MET + SN-trees submitted to the combined exposure to metamitron application and shading nets. Low radiation significantly increased metamitron absorption (36–53% in the three locations in 2018) and reduced its degradation. Net photosynthesis and stomatal conductance were strongly reduced in all treatments, with minimum values 2 days after spraying (DAS) and incomplete recovery 10 DAS in MET + SN. All treatments resulted in leaf sucrose and sorbitol decreases, leading to a negative carbon balance. SN and MET + SN promoted the highest thinning e cacy, increasing fruit weight and size, with MET + SN causing over-thinning in some trials. Leaf antioxidant enzymes showed moderate changes in activity increases under MET or MET + SN, accompanied by a rise of glutathione content and a reduction in ascorbate, however without lipid peroxidation. This work shows that environmental conditions, such as cloudy days, must be carefully considered upon metamitron application, since the low irradiance enhances metamitron e cacy and may cause over-thinning